De novo assembly and comparative analysis of the first complete mitogenome in Distylium (Distylium racemosum) - Wang, Yaling; Zhang, Zhongxiao; Chen, Xinru; Li, Honghe; Ma, Chi; Guo, Penghui (Frontiers in Plant Science, 2025)
The genus Distylium (Hamamelidaceae) is highly valued for its applications in ornamental horticulture, industry, and construction. Although plastid genomes (plastomes) of multiple Distylium species have been characterized, no mitochondrial genomes (mitogenomes) have been reported for this genus. In this study, we assembled and annotated the complete mitogenome of Distylium racemosum using HiFi sequencing data. The mitogenome comprises a longer circular chromosome and a shorter linear chromosome (904,264 bp in total length), revealing a structurally complex conformation. We annotated 67 genes, including 43 protein-coding genes (PCGs), 21 tRNA genes, and three rRNA genes. Analyses identified exceptionally high repetitive sequence content, with 304 simple sequence repeats, 1,508 dispersed repeats, and 50 tandem repeats, representing the highest repeat content among Saxifragales mitogenomes to date. Additionally, 49 mitochondrial plastid DNA sequences were detected, including only one complete plastid-derived gene (trnC-GCA) transferred to the mitogenome. We predicted 697 RNA editing sites across 42 PCGs, further underscoring the genome’s dynamic evolution. Phylogenetic reconstruction based on mitogenomes and plastomes from 18 species indicated D. racemosum occupied a basal position within Saxifragales, which is consistent with the APG IV classification system. This study provides the first comprehensive mitogenomic resource for the Distylium genus, offering valuable insights for molecular classification, species identification, and germplasm conservation of Distylium plants.